Compressed concrete block using crushed laterite brick as sand substitution - Che Amri, Che Azmi (2012)
During last decades, it has been recognized with growing concern that wastes from a construction are of large volume and that this volume is increasing year by year The problem of waste accumulation exists worldwide. Most of waste materials are left as a landfill materialor illegally dumped. Environmental impact can be reduced by making more sustainable use of this waste by recycling process. Main objectives of this research are to determine the mechanical properties of crushed laterite brick and also to determine the compressive strength of concrete block using crushed laterite brick as sand substitution. Based on these two objectives, all sample will undergoes certain process starts from finalizing mix design, then followed by preparing samples that covered sieving, batching, mixing, compacting and end with curing process. At age l days and 28 days all sample will betested on their compressive strength by compressive test method.. Data obtained from compressive test shows that by substituting sand with crushed laterite brick, the strength of concrete block can be enhance: As a conclusion crushed laterite bricks meets all the requirements to be used as sand substitution in concrete block.